Discourse Fragmentation of Pesta Babi Documentary Audiences: A Social Network Analysis on YouTube - Syah, Ady Adnan; Yusanto, Freddy; Nugroho, Catur (UIR Press, 2026)
The screening of the documentary film Pesta Babi: Kolonialisme di Zaman Kita (Pig Feast: Colonialism in Our Time) on YouTube in May 2026 triggered thousands of comments from viewers across Indonesia. This study analyzes how conversation patterns formed in the comment section, and specifically whether they constituted a balanced discussion space or instead became fragmented into groups that did not engage in dialogue with one another. Using Social Network Analysis (SNA) through YouTube Data Tools (YTDT) and Gephi, data from 28,328 comments and 5,525 user interactions were mapped into a visual network. The results reveal a very sparse network (density 0.01), divided into 41 disconnected components, with 50 discourse clusters and a modularity score of 0.472. All five of the largest clusters exclusively represented pro-film and pro-Papua discourse, and not a single cluster was found that consistently supported government policy. Even an account that self-identified as a member of the Indonesian National Armed Forces (TNI) confirmed the film's truthfulness. Although discourse fragmentation in digital public spheres has been widely studied, no prior research has applied SNA to YouTube comments of indigenous rights documentary films in Indonesia. These findings are interpreted through Habermas's public sphere theory. Rather than serving as an arena for rational and balanced discussion, the YouTube comment section of the Pesta Babi film instead reveals discourse fragmentation that is ideologically consolidated, a condition the researchers characterize as a deliberative illusion.